Menyajikan Berbagai Insiden Cybercrime yang Terjadi di Indonesia, Termasuk Pencurian Data dan Peretasan Situs Web Pemerintah - Seri Mughni Sulubara (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This research aims to explore how cybercrime occurs in Indonesia and the government's efforts to tackle it. By understanding the various incidents that occur and the factors that cause them, it is hoped that this research can contribute to the development of policies and prevention strategies that are more effective in dealing with cybercrime threats. The research method used is descriptive qualitative research with a normative juridical approach. Qualitative descriptive research with a normative juridical approach is research that tries to describe an event or incident that occurs directly, real, realistic, actual in the existing rules. The results and discussion of this research show that cybercrime, especially data theft and hacking of government websites, is a serious problem that requires immediate attention and action. With the right measures, it is hoped that Indonesia can reduce cybercrime incidents and improve overall cybersecurity. Overall, the results of this study provide a comprehensive overview of the challenges Indonesia faces in dealing with cybercrime threats as well as the steps that need to be taken to improve cybersecurity in the country.